Emprego de turfa e resíduo de angico branco (Anadenanthera colubrina) na remediação de btex em água produzida - Costa, André Silveira (2011)
Petroleum exploration, an activity that generates economic benefits, can also bring environmental impacts, one of which associated with large quantities of produced water discharged into aquatic environments. A particular concern is that these discharges contain significant amount toxic compounds including benzene, toluene, ethylbenzene and isomers of xylene (BTEX). One option to be employed to minimize the concentrations of these compounds entering the environment is to treat the water prior to discharge. The present work therefore investigates the potential of peat and angico sawdust to remove BTEX from produced water. Samples of produced water was collected from the Bonsucesso treatment station, operated by Petrobras in of Carmópolis City, Brazil. In batch experiments, the removal capacity of the peat was 32.4, 50.0, 63.0, 67.8 and 61.8% for benzene, toluene, ethylbenzene, m,p-xylene and oxylene, respectively. Comparing with removal capacities of angico sawdust of 20.2, 36.4, 52.8, 57.8 and 53.7% for these compounds, respectively, peat has show a superior performance of removal. Identification and quantification of BTEX was done by gas chromatography. After optimization, accuracy exceeding 90 %, precision better than 6 %, linear determination coefficient (r2) of 0.998, and limits of detection and quantification of 0.09-0.18 μg L-1 and 0.27-0.35 μg L-1, respectively. This work has demonstrated considerable potential of alternative materials for efficient removal of organic compounds from aqueous media.